PERANAN AUDIT OPERASIONAL UNTUK MENINGKATKAN KINERJA FUNGSI PEMASARAN PT MNC FINANCE, Tbk. - Anam, David Faizal (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out how the implementation of operational audit is in order to improve the marketing functions performance at PT MNC Finance, Tbk. This research is using descriptive qualitative to describe how the implementation of operational audit is in order to improve the performance of marketing functions, at PT MNC Finance Tbk. The data is using both primary and secondary data which is obtained from Marketing department and Internal audit of PT MNC Finance, Tbk., Tulungagung, East Java branch. The result of research shows that the operational audit has been implemented appropriately in accordance with the regulations which have been set by the Internal Audit Division of PT MNC Finance, Tbk. and operational audit has the role in increasing the marketing functions of PT MNC Finance, Tbk. It can be seen from the data of marketing performance has been increasing in the year of 2012 as much as 8.5% or equal to Rp 1,543,000,000.Keywords: Operational Audit, Performance, Marketing Function